ChemInform Abstract: Pd‐Catalyzed Isocyanide Insertion/Nucleophilic Attack by Indole C‐3/Desulfonylation in the Same Pot: A Direct Access to Indoloquinolines of Pharmacological Interest. Issue 49 (December 2015) - Prasad, Bagineni; Nallapati, Suresh Babu; Kolli, Sunder Kumar; Sharma, Atul Kumar; Yellanki, Swapna; Medisetti, Raghavender; Kulkarni, Pushkar; Sripelly, S.; Mukkanti, K.; Pal, Manojit
Abstract: Several of the title compounds show promising cytotoxicities against cancer cells.